EMPOWERING WOMEN THROUGH AIRWAVES: A COMPARATIVE ANALYSIS OF WOMEN-CENTRIC PROGRAMMING ON ALL INDIA RADIO AND MY FM 94.3 - Raghuwanshi, Anuja; Chaturvedi, Dr. Vanya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Radio, which is called the medium of sound, is actually working like a magic into listeners ears the reason is voice, presentation, language, tone of the artists and its content. Radio is the most important program content that engages the audience and has always been working to create awareness and educate the society. There has been an old relationship between radio and women. Radio has been broadcasting programs for women for many years, but with time there have been many changes in the program content, through which we have tried to know what kind of content the radio channels are now broadcasting for women. Are they relevant to women empowerment? or their main objective just to entertain? For the study, we have selected a private radio channel (94.3 MY FM) and a public radio channel (All India Radio). To know about women empowerment content, we have included women centric programs of both the channels for the study. The study area is city of lakes Bhopal (Madhya Pradesh). This is the one-week radio shows study in which researcher has recorded one-week women-based radio shows on mobile phone. We have analyzed the study content very deeply. The researcher also tried to know how much time slot they are giving for women centric shows. As well as to know what the difference between the two is, for which we have used a comparative study methodology to get better results.